2020
DOI: 10.1017/s0007114520004006
|View full text |Cite
|
Sign up to set email alerts
|

Changes in human milk fatty acid composition and maternal lifestyle-related factors over a decade: a comparison between the two Ulm Birth Cohort Studies

Abstract: Human milk fatty acid composition varies during lactation and is influenced by maternal diet, maternal lifestyle-related factors and genetic background. This is one of the first studies to investigate a period effect, i.e. the impact of lifestyle-related changes on human milk fatty acid composition, in two different cohorts. Lactating women were recruited from the general population a decade apart in Ulm, Germany, using similar methodology. Human milk samples collected 6 weeks post-partum were analysed [Ulm Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…31 This combined with an overall higher PUFA intake over the years could indicate that they have consumed or taken fish oil/n-3 fatty acid supplements. 31 On the other hand, we also cannot rule out that the small sample size in our study could have led to a potential chance finding. It is therefore plausible that if the study were larger, this chance effect would be less likely to occur.…”
Section: Sex Differences In Relative Dha Proportions At 6 Monthsmentioning
confidence: 99%
“…31 This combined with an overall higher PUFA intake over the years could indicate that they have consumed or taken fish oil/n-3 fatty acid supplements. 31 On the other hand, we also cannot rule out that the small sample size in our study could have led to a potential chance finding. It is therefore plausible that if the study were larger, this chance effect would be less likely to occur.…”
Section: Sex Differences In Relative Dha Proportions At 6 Monthsmentioning
confidence: 99%
“…The percentage of fatty acids in breast milk is affected by several factors, including maternal diet (53,111,112). Studies have found that maternal dietary intake affects SFAs such as capric acid, lauric acid, myristic acid, MUFAs such as oleic acid, and PUFAs such as EPA, DHA, LA, and ALA (112)(113)(114)(115)(116)(117)(118). Collectively, these studies show that the diet of lactating mothers is a very potent mediator of breast milk lipid composition during lactation.…”
Section: Maternal Factors Affecting Fatty Acid Composition In Breast ...mentioning
confidence: 99%
“…93 As the concentrations of these two FAs rise, that of the longer FAs decreases. 94 Early FAs may also be derived from extramammary sources, but the breast then quickly begins to synthesize these. 95 The total fat content in milk may have a predictive value; 90% of the women whose milk contained ≥20 grams fat per feeding on postnatal day 7 were successfully breastfeeding 3 months later.…”
Section: Saturated Fas In Hmmentioning
confidence: 99%